Comparative assessment of the surface properties of Ukrainian ash microspheres - Berehovyi, Taras; Sviderskyi, Valentin (Technology audit and production reserves, 2023)
The object of research is ash microspheres from the burning of hard coal in Donetsk, Lviv-Volyn (Ukraine) and foreign (South Africa) basins, power plants of various regions. The chemical and mineralogical composition of Ukrainian ash microspheres was analyzed in comparison with foreign counterparts (South Africa, Great Britain, etc.), other types of microspheres (glass, ceramic) and expanded perlite. The advantages of aluminosilicate microspheres of technogenic origin (ASM) over other lightweight fillers are noted. One of the most problematic areas is the lack of an objective comparative assessment of Ukrainian ash microspheres in terms of the influence of the structure-forming bonds Si–O, Si–O–Si and Si–O–Al on the physicochemical properties and energy and reactivity of their surface. It was established that the SiO2/Al2O3 ratio in their composition is within 1.46–1.87 against 1.53–1.64 in South African ASM and 4.81–5.61 in swollen pearlites, which ensures the content of crystalline phases (mullite, quartz) from 36 wt. % in Trypil microspheres to 53 wt. % in Kurakhove microspheres. The latter have a minimal content of Si–O–Si bonds (the I0/I ratio in the 1029 cm–1 band is 1.25 versus 6.71 in Burstyn ASM). The revealed features of changes in the chemical and mineralogical composition of microspheres, as well as structure-forming bonds, are fully correlated with the content of adsorbed water and OH and CH groups in the surface layer of the latter and, as a result, the energy state and reactivity of ASM. A quantitative assessment of their wettability with water (0.32–0.106) and under the condition of tgδ (0.196–0.4490) is given. The availability of such information makes it possible to clearly classify Ukrainian ash microspheres according to the degree of efficiency of use, taking into account their advantages in the composition of composite materials on various types of binders and to assess the presence of interchangeability in the context of a special situation in Ukraine.